ANALISIS NILAI TAMBAH DAN KELAYAKAN USAHA PENGGILINGAN PADI DI KECAMATAN BUAY BAHUGA, KABUPATEN WAY KANAN, LAMPUNG (JASEP, 2020)
Buay Bahuga Sub-district Way Kanan District has a small-scale rice milling business that is processing rice into consumption-ready rice which operates every rice harvest season between March and September, so that the production of rice produced can meet the needs of rice consumption at the district, district and level. The total production costs of rice milling business from 2015 to 2017 consisted of fixed costs and variable costs, namely in 2015 the use of production costs was Rp 800,006,105 / year, in 2016 Rp 686,885,083 / year, and 2016 was in the amount of Rp. 568,994,683 / year with the use of production costs as much as Rp. 2,057,937,672. Based on the table above, the revenue of rice milling business in 2015 was Rp 578,239,200. with the use of a fee of Rp. 382,505,680, the added value of the rice milling business in 2016 was Rp. 188,279,360. In 2015 revenues of Rp 977,961,600 and costs between Rp. 657,957,000 then the added value is Rp. 296,077,200. In 2017, the revenue was Rp. 814,968,000 with the use of costs between Rp. 547,555,200 so the value added in the business of making rice flour in 2017 was Rp. 256,768,320. The total production of rice milling business is 75,096 kg / year with a selling price of Rp 7,700 / kg, business revenue is obtained at Rp 578,239,200, the use of production costs is Rp 800,006,105, then an income of Rp -221,766,905 is obtained. Added value to the rice milling business in the Buay Bahuga District Rp. 578,239,200. with the use of a fee of Rp. 382,505,680, the rice milling business in Buay District is also feasible to be developed financially.